Exploring The Impact of E-CRM System on Customers in Banking Sector Using PLS-SEM Approach - Mohamed , Shymaa Mohamed; Marie , Mohamed; Yehia, Engy (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The banking sector has faced a variety of difficulties in the competitive business environment. The adoption of electronic means by banks is a requirement for them to meet these problems and keep customers satisfied. Through different electronic touch points, E-CRM aids in establishing and preserving mutually beneficial long-term connections with customers. This study aims to understand the effects of E-CRM on customer satisfaction, loyalty, and trust in the banking industry. Customers of banks using E-CRM services filled out questionnaires to help with this. Partial Least Squares Structural Equation Modeling (PLS-SEM) was utilized to evaluate the study model using the data that were collected through a survey. The first results revealed that E-CRM had strong effect on service quality, trust, and customer satisfaction while very week effect on customer loyalty. We performed an enhancement of the research model throw two phases, and the results proved that enhancing E-CRM systems positively affects customer satisfaction and loyalty when quality and trust are put as a mediator for them.